PENGEMBANGAN PERANGKAT PEMBELAJARAN KONTEKSTUAL PADA PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 CURUP KABUPATEN REJANG LEBONG - Kusen, Kusen (State Institute for Islamic Studies Batusangkar, 2016)
Islamic Education as one of the subjects in SMP N 1 Curup Rejang Lebong has a strategic role in the formation of character and personal student. Based on initial observations are students who reflect the character despicable character. This research aims to develop the contextual learning in Islamic education in SMP N 1 Curup Rejang Lebong in class VII Semester 1 through Contextual learning Valid, practical and effective. Subject or informan in this study conducted on students SMP N 1 Curup Rejang Lebong class VII. This research is the development of procedural composed of ten steps, namely: (1) identification of the problem, (2) the collection of information, (3) design prodik, (4) design validation, (5) the improvement of design, (6) the trial product , (7) the revision of the product, (8) utility testing, (9) the revision of the final stage of product, 10) mass production, in order to obtain the syllabus, teaching implementation plan, module and student worksheet valid, practical and effective. The subjects were SMP N 1 Curup Rejang Lebong. Data was collected through observation, questionnaires, and test results. Data were analyzed by percentage. The results of this study are: syllabus, teaching implementation plan, modules and Student Worksheet that has been validated by the validator is valid. Then based on the responses of students to the modules and worksheets Islamic Religious Education class VII SMP. Curup Rejang Lebong is practical.Teaching plan implementation, modules and Student Worksheet provided in the learning process is effective.Kewords: Learning Instruction, Contextual Teaching Learning, Islamic Education